Penerapan pembelajaran kooperatif tipe STAD untuk meningkatkan hasil belajar matematika - I Komang Gede Sudarsana (Indonesian Journal of Educational Development, 2021)
This research is a classroom action research which is conducted with the aim of improving student learning outcomes in mathematics through the application of the STAD type cooperative learning model. The subjects of the study were 20 students of class IXG SMP Negeri 1 Bebandem in the academic year 2019/2020, consisting of 12 male students and 8 female students, while the object of this study was the result of learning mathematics. The learning outcome data were collected by means of tests and then analyzed based on the learning achievement and learning mastery. The indicator of success in this study is that students achieve ≥ 72% learning achievement with learning mastery ≥ 85%. This research was conducted in two cycles and gave a very thrilling results. In cycle I, the learning achievement achieved by students is 76,50% with learning mastery 75,00% and in cycle II the learning achivement achieved by students is 80,50% with learning mastery 85,00%. From these results it can be seen that there is an increase in the learning achievement capacity of 4,00% and an increase in learning mastery by 10,00%. Based on the results obtained, it can be concluded that the application of the STAD type cooperative learning model can improve the mathematics learning outcomes of class IXG students of SMP Negeri 1 Bebandem in the academic year 2019/2020. Penelitian ini merupakan penelitian tindakan kelas yang dilaksanakan dengan tujuan untuk meningkatkan hasil belajar siswa dalam pelajaran matematika melalui penerapan model pembelajaran kooperatif tipe STAD. Subjek dari penelitian adalah siswa kelas IXG SMP Negeri 1 Bebandem Tahun Pelajaran 2019/2020 berjumlah 20 orang terdiri dari 12 orang siswa laki-laki dan 8 orang siswa perempuan sedangkan objek dari penelitian ini adalah hasil belajar matematika. Data hasil belajar dikumpulkan dengan tes selanjutnya dianalisis berdasarkan daya serap dan ketuntasan belajar. Indikator keberhasilan dalam penelitian ini adalah daya serap siswa mencapai ≥ 72% dengan ketuntasan belajar ≥ 85%. Penelitian ini dilaksanakan dalam dua siklus dan memberikan hasil yang sangat menggembirakan. Pada siklus I daya serap yang dicapai siswa 76,50% dengan ketuntasan 75,00% dan pada siklus II daya serap yang dicapai siswa 80,50% dengan ketuntasan 85,00%. Dari hasil tersebut dapat diketahui ada peningkatan daya serap sebesar 4,00% dan peningkatan ketuntasan belajar sebesar 10,00%. Berdasarkan hasil yang diperoleh dapat disimpulkan bahwa penerapan model pembelajaran kooperatif tipe STAD dapat meningkatkan hasil belajar matematika siswa kelas IXG SMP Negeri 1 Bebandem Tahun Pelajaran 2019/2020.